Blackout - Rocco, John. (New York : Disney/Hyperion Books, 2011)
When a busy family's activities come to a halt because of a blackout, they find they enjoy spending time together and not being too busy for once.
Caledecott Honor, 2012.
Keywords: Electric power failures -- Juvenile fiction; Families -- Juvenile fiction